2021
DOI: 10.1177/17562864211054157
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of immunosuppressive therapy in myelin oligodendrocyte glycoprotein antibody–associated disease: a systematic review and meta-analysis

Abstract: Background: A considerable number of patients with myelin oligodendrocyte glycoprotein antibody–associated disease (MOGAD) will experience a relapse, but the effect of maintenance therapies on re-attack rates is currently unknown. Objective: To investigate the efficacy and safety of immunosuppressive therapy for preventing disease relapses in patients with MOGAD, including rituximab (RTX), mycophenolate mofetil (MMF), and azathioprine (AZA). Methods: English-language studies published prior to August 31, 2020,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…Our meta-analysis shows that RTX treatment is effective in reducing the relapse rate and improving neurological disability in patients with MOGAD. This is in line with previous systematic reviews, where the efficacy of several immunotherapies—including RTX—was assessed in patients with MOGAD 68–70. In addition, we found that the ARR reduction was consistent across all subgroups of patients analysed.…”
Section: Discussionsupporting
confidence: 91%
“…Our meta-analysis shows that RTX treatment is effective in reducing the relapse rate and improving neurological disability in patients with MOGAD. This is in line with previous systematic reviews, where the efficacy of several immunotherapies—including RTX—was assessed in patients with MOGAD 68–70. In addition, we found that the ARR reduction was consistent across all subgroups of patients analysed.…”
Section: Discussionsupporting
confidence: 91%
“…Acute treatment should follow published recommendations and guidelines. If high-dose IVMP does not lead to rapid and complete or almost complete resolution of symptoms, escalatory PLEX is often required; sometimes IVIG is used, especially in children [ 11 , 26 ]. It should be noted that MOG-EM-associated symptoms may be steroid-dependent; OS therapy with tapering is therefore commonly used after IVMP.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that MOG-EM-associated symptoms may be steroid-dependent; OS therapy with tapering is therefore commonly used after IVMP. Whether long-term immunosuppressive/immunomodulatory therapy (often with azathioprine, rituximab, MMF or, especially in children, IVIG) is required depends on clinical presentation, attack severity, the degree of symptom resolution after acute therapy, and on whether relapses occur [ 11 , 26 , 45 ]. More needs to be learned about the long-term treatment needs of patients with postvaccinal MOG-EM.…”
Section: Discussionmentioning
confidence: 99%
“…15,38 Strikingly, LP use during the NMOSD diagnosis process was found in 91% and positivity for OCB in 25%, consistent with previous data. 1,2 There is solid evidence that MS DMDs such as interferons, natalizumab, fingolimod, and alemtuzumab, which are usually used to treat MS patients, are ineffective in NMOSD patients (including MOGAD patients) 39 and can even increase annualized relapse rates. 6 Likewise, MS DMDs have a significant economic burden with potential serious adverse effects.…”
Section: Discussionmentioning
confidence: 99%